2014
DOI: 10.1136/bmjopen-2014-005785
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in stillbirths at term after new birth induction paradigm: results of a national intervention

Abstract: ObjectiveThe risk of fetal death increases steeply after 42 gestational weeks. Since 2009, Denmark has had a more proactive policy including prevention of prolonged pregnancy, and early intervention in women with diabetes, preeclampsia, high body mass index and of a higher age group. The aim of this study was to describe the development in fetal deaths with this more proactive birth induction practice, and to identify and quantify contributing factors for this development.DesignNational cohort study.SettingDen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 24 publications
4
41
0
Order By: Relevance
“…5 The present study demonstrates that the reduction in stillborn infants was followed by significant reductions in newborn asphyxia, neonatal mortality, newborn macrosomia and peripheral nerve injuries. The incidence rate of admission to neonatal intensive care units increased, but only in neonates born after planned vaginal delivery or elective caesarean section and not in neonates born after labour induction.…”
Section: Main Findingsmentioning
confidence: 51%
See 2 more Smart Citations
“…5 The present study demonstrates that the reduction in stillborn infants was followed by significant reductions in newborn asphyxia, neonatal mortality, newborn macrosomia and peripheral nerve injuries. The incidence rate of admission to neonatal intensive care units increased, but only in neonates born after planned vaginal delivery or elective caesarean section and not in neonates born after labour induction.…”
Section: Main Findingsmentioning
confidence: 51%
“…Awareness of the dangers related to smoking has grown, 35 explaining the significant reduction in pregnant smokers; this reduction contributed significantly to the decrease in stillbirths but only marginally to reductions in the perinatal outcomes described in this study. 5 The increased maternal age, greater nulliparity and higher body mass index indicated that more women were at risk according to time in our study population, suggesting that the crude results reported have underestimated the positive effect of labour induction. 36 However, adjusting for these factors only changed the results minimally.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our results are supported by another Danish study, where the risk of stillbirth from 37 to 40 weeks were studied in 2000-2012. They found a generally decreasing risk of stillbirth in term pregnancies in Denmark throughout the years studied (14). Furthermore, an American study from 2011 using a cost effectiveness model based on the literature concluded that elective induction of labor at 41 weeks is cost-effective and improves outcomes (15).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of labor has increased significantly over the past decades . The rate of induced labor in Denmark has increased by 108% from 12.4% in 2000 to 25.1% in 2012, with labor induction occurring in one out of four deliveries . In 2011, the Danish Obstetrical Society changed the national guidelines regarding post‐term routine labor induction and intensified late‐pregnancy surveillance.…”
Section: Introductionmentioning
confidence: 99%